Incapacitating pain from Tenofovir Induced Hypophosphatemic Osteomalacia in a Hemophilia Patient - A Case Report - Emma Woo; Dinesh Kumbhare; Paul Winston (Taylor & Francis Group, 2020)
Background: Pain in patients with hemophilia is common and usually a result of arthropathy. Clinicians should, however, consider a wide range of etiologies for pain in patients with hemophilia including infection, osteoporotic fractures, arthritis, and osteomalacia. Aims: This case demonstrates an instance of poorly localized back and hip pain, severe enough to prevent ambulation, caused by hypophosphatemic osteomalacia due to tenofovir treatment for blood transfusion acquired Human Immunodeficiency Virus (HIV) in a patient with hemophilia A. Methods: Case Report. Results: With termination of tenofovir treatment, this patient returned to baseline function. Conclusion: This report serves to emphasize the need for accurate diagnosis of pain in hemophilia patients, especially among the aging demographic of people with hemophilia in which there is a significant likelihood of an HIV infection and among patients who may be on Pre-exposure Prophylaxis (PrEP) or clinical trials involving tenofovir.